Determinants of trust on zakat institutions and its dimensions on intention to pay zakat: A pilot study - Muhammad, S. A.; Saad, Ram Al Jaffri (Akademia Baru, 2016)
Survival of voluntary organizations depends on the level of trust donors has on that particular institution.Zakat payment to zakat institution in many Muslim countries is the choice of zakat payer either to pay to zakat institution or not. Based on this reason, the survival of zakat institution has a direct relationship with the level of trust vested in zakat institutions by contributors of zakat fund.Therefore, it is important to know the dimension of trust on zakat institution and their reliability assessment.This study aims at investigating the reliability and validity of trust’s dimension and its relationship on intention to pay zakat in Kano Nigeria.The study concludes that items of public governance quality, quality of zakat distribution, service quality and perceived board capital are reliable and valid. Therefore, the study recommends that all the items can be used in the main study and another related area.